Relationship between Pain and Plasma Amino Acid Levels in Chronic Pancreatitis - Kawaguchi, Yoshiaki; Lin, Jung-Chun; Kawashima, Yohei; Maruno, Atsuko; Ito, Hiroyuki; Ogawa, Masami; Mine, Tetsuya (JOP. Journal of the Pancreas, 2015)
Objective Our aim was to investigate the relationship between imbalances of plasma amino acids and pain in chronic pancreatitis (CP). Methods Thirty patients with alcoholic CP in an exocrine-insufficient state were examined. We divided them between diet and control group. Diet group ingested 80g/300kcal of the elemental diet "Elental®". This diet of 300 kcal/day was administered for two months. Selected clinical and laboratory values were compared between both groups before and after diet. Pain was observed and compared using a visual analog scale (VAS). Results There was no significant difference in the BMI between both groups before and after diet. The serum albumin level in diet group after diet was significantly higher than in control group (P=0.036). There was no significant difference in HbA1c between both groups before and after diet. The total amino acid concentration was significantly higher in diet group after diet than in control group (P=0.033). The concentrations of serum histidine and methionine in diet group after diet were significantly higher than in control group (histidine, P=0.022; methionine, P=0.026). The concentration of serum glutamate in diet group after diet was significantly lower than in control group (P=0.027). The balance of amino acids in diet group was normalized after the Elental® was ingested. The VAS score was significantly lower in diet group after diet than in control group (P=0.018). Conclusion These amino acid levels and pancreatic pain were improved by the elemental diet. The pancreatic pain may be related to these amino acid imbalances. Image: Tokai University Hospital. Isehara, Japan